(untitled) (Archives of Mechanics - Test, 2006)
Normal shock wave, terminating a local supersonic area on an airfoil, not only limits aerodynamic performance but also becomes a significant source of a high-speed impulsive noise on the rotor blade of a helicopter. It is proposed to apply passive control to disintegrate the shock wave by smearing pressure gradients created by the shock. Details of the flow structure obtained by this method are studied numerically. A new boundary condition of a perforated wall is verified against experimental data for a passive control of the shock wave in a channel flow and on an airfoil. This method of shock wave disintegration is proven to work for internal flows in transonic nozzles and appears to be effective for transonic airfoils as well. The substitution of a shock wave by a gradual compression changes completely the source of the high-speed impulsive noise and bears potential of its reduction.